Classification for Covid-19 Affected Family Cash Aid Recipients Using Naïve Bayes Algorithm - Mutiara Amazona Sosiawati; Syafriandi Syafriandi; Dony Permana; Zilrahmi (Departemen Statistika Universitas Negeri Padang, 2023)
The COVID-19 pandemic that occurred in Indonesia had a huge impact on the country's economy. One of the solutions set by the government in dealing with COVID-19 is to use APBD funds for social assistance in the form of cash, namely